A Disintegrin and Metalloprotease 17 in the Cardiovascular and Central Nervous Systems - Xu, Jiaxi; Mukerjee, Snigdha; Silva-Alves, Cristiane R. A.; Carvalho-Galvão, Alynne; Cruz, Josiane C.; Balarini, Camille M.; Braga, Valdir A.; Lazartigues, Eric; França-Silva, Maria S. (Frontiers in Physiology, 2016)
ADAM17 is a metalloprotease and disintegrin that lodges in the plasmatic membrane of several cell types and is able to cleave a wide variety of cell surface proteins. It is somatically expressed in mammalian organisms and its proteolytic action influences several physiological and pathological processes. This review focuses on the structure of ADAM17, its signaling in the cardiovascular system and its participation in certain disorders involving the heart, blood vessels and neural regulation of autonomic and cardiovascular modulation.